2018
DOI: 10.1038/s41593-018-0206-1
|View full text |Cite|
|
Sign up to set email alerts
|

GWAS of lifetime cannabis use reveals new risk loci, genetic overlap with psychiatric traits, and a causal effect of schizophrenia liability

Abstract: Cannabis use is a heritable trait that has been associated with adverse mental health outcomes. In the largest genome-wide association study (GWAS) for lifetime cannabis use to date (N = 184,765), we identified eight genome-wide significant independent single nucleotide polymorphisms in six regions. All measured genetic variants combined explained 11% of the variance. Gene-based tests revealed 35 significant genes in 16 regions, and S-PrediXcan analyses showed that 21 genes had different expression levels for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
455
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(527 citation statements)
references
References 77 publications
(102 reference statements)
23
455
7
2
Order By: Relevance
“…Although results from the discovery GWAS for cannabis use were genetically correlated with risk-taking (SNP-r g = 0.425, P = 3.4e-42) [19], we found no evidence that our measures of risk-taking were consistently related to the cannabis use PRS. Even though PRS were correlated with conduct disorder, associations between the PRS and trajectory membership persisted even after controlling for conduct disorder.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Although results from the discovery GWAS for cannabis use were genetically correlated with risk-taking (SNP-r g = 0.425, P = 3.4e-42) [19], we found no evidence that our measures of risk-taking were consistently related to the cannabis use PRS. Even though PRS were correlated with conduct disorder, associations between the PRS and trajectory membership persisted even after controlling for conduct disorder.…”
Section: Discussioncontrasting
confidence: 70%
“…Effect sizes and effect alleles were derived from genomewide summary statistics from a large GWAS meta-analysis of 162 082 individuals, all of European ancestry (characteristics of discovery GWAS [19] in Supporting information). PRS were created for each COGA individual of genetically verified European descent with SNPs meeting increasingly lenient P-value thresholds from the discovery GWAS (from P T < 0.0001 to P T < 0.50).…”
Section: Polygenic Risk For Cannabis Usementioning
confidence: 99%
“…The ANYDEP phenotype is particularly well suited for this ascertained sample as drug dependence more commonly co-occurs with alcohol dependence than with dependence on any other substance. 11 Finally, given the proposed role of reward-related neural response in the etiology of addiction, 27,28 we examined whether GWS loci were correlated with reward-related ventral striatum reactivity as measured with blood-oxygen-level dependent (BOLD) functional magnetic resonance imaging (fMRI) in the independent Duke Neurogenetics Study (EA n = 481, AA n = 118). For genomewide significant (GWS) associations, we performed secondary analyses evaluating associations with individual alcohol and drug dependence diagnoses, and to examine whether the exclusion of those cases who met criteria only for alcohol dependence altered the association.…”
Section: Introductionmentioning
confidence: 99%
“…A significant genetic correlation between cannabis use and depression was observed in an extended pedigree sample [15], but with a discordant twin design, genetic factors played only a small role in the link between early or frequent cannabis use and depression [16]. In unrelated samples, cannabis use was associated with polygenic risk for depression [17]; however, using genome-wide summary statistics to consider the genetic correlations between cannabis use and a range of genetic traits, the estimated correlation with depression was modest, but not significant [13]. In the latter two analyses, the underpowered (and since superseded) PGC-MDD 2013 depression sample [18] was used, which is likely to have impacted upon results.…”
Section: Introductionmentioning
confidence: 98%
“…Both cannabis use [11] and depression [12] are known to be heritable, and substantial increases in sample sizes mean that there has been progress in understanding the genetic basis of these phenotypes individually. For cannabis use, the largest genome-wide association (GWA) study to date reported eight significant loci [13], and for depression, 44 genome-wide significant loci were identified by the Psychiatric Genomics Consortium Major Depressive Disorder (PGC-MDD) working group and 23andMe [14]. These univariate findings provided a foundation to research the genetic interplay between these comorbidity traits.…”
Section: Introductionmentioning
confidence: 99%